Studi Perbandingan Layanan Cloud Computing - Afdhal Afdhal (Jurnal Rekayasa Elektrika, 2013)
In the past few years, cloud computing has became a dominant topic in the IT area. Cloud computing offers hardware, infrastructure, platform and applications without requiring end-users knowledge of the physical location and the configuration of providers who deliver the services. It has been a good solution to increase reliability, reduce computing cost, and make opportunities to IT industries to get more advantages. The purpose of this article is to present a better understanding of cloud delivery service, correlation and inter-dependency. This article compares and contrasts the different levels of delivery services and the development models, identify issues, and future directions on cloud computing. The end-users comprehension of cloud computing delivery service classification will equip them with knowledge to determine and decide which business model that will be chosen and adopted securely and comfortably. The last part of this article provides several recommendations for cloud computing service providers and end-users.